Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T16:42:33+01:00
A)2z+t-3z+4t-1 dla z=5 i t=0,1
2z+t-3z+4t-1=-z+5t-1=-5+5*0,1-1=-6+0,5=-5,5

b)13x-2y+7-9x+y-4+x-3 dla x=0,2,y=-1
13x-2y+7-9x+y-4+x-3=5x-y=5*0,2+1=2

c)n'2+n-7+3n'2-n-9-n+16 dla n=-1/2
n'2+n-7+3n'2-n-9-n+16=4n^2-n=4(-1/2)^2+1/2=4*1/4+1/2=1+1/2=3/2=1 i 1/2
2 3 2
2010-01-25T16:42:53+01:00
2z+t-3z+4t-1 z=5i t=0,1
REDUKCJA
2z-3z+4t+t-1
-x+5t-1
Działanie
-5+5*0,1-1=-5,5




13x-2y+7-9x+y-4+x-3 dla x=0,2,y--1
REDUKCJA
13x+x-9x-2y+y+7-4-3
5x-y
Działanie
5*0,2+1=2




n'2+n-7+3n'2-n-9-n+16 dla n=-1/2
REDUKCJA
n²+3n²+n-n-n-7-9+16
4n²-n
Działanie
4*(-½)²-(-½)
4*1/4+½=1½
3 2 3
2010-01-25T16:43:29+01:00
A)2z+t-3z+4t-1 dla z=5i t=0,1
-1z+5t-1=
-1*5+5*0,1-1=
-5+0.5-1=
-5,5
b)13x-2y+7-9x+y-4+x-3 dla x=0,2,y--1
5x-1y=
5*0,2-1*(-1)=
1+1=
2
c)n'2+n-7+3n'2-n-9-n+16 dla n=-1/2
2n'2-n=
2*1/4-1/2=
0,5-0,5=
0
3 2 3